Firm acquisitions by family firms: A mixed gamble approach - Katrin Hussinger; Abdul-Basit Issah (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
This study elucidates the mixed gamble confronting family firms when considering a related firm acquisition. The socioemotional and financial wealth trade-off associated with related firm acquisitions as well as their long-term horizon turns family firms more likely to undertake a related acquisition than non-family firms, especially when they are performing above their aspiration level. Post-merger performance pattern confirm that family firms are able to create long-term value through these acquisitions and by doing so they surpass non-family firms. These findings stand in contrast to commonly used behavioural agency predictions, but can be reconciled with theory through a mixed gambles' lens.
Keywords: G34; L10; L20; M20; 330; firm acquisitions; related firm acquisitions; mixed gamble; aspiration level; socioemotional wealth; value creation